Towards sustainable aquaculture in the Amazon - Pacheco, Felipe S.; Heilpern, Sebastian A.; DiLeo, Claire; Almeida, Rafael M.; Sethi, Suresh A.; Miranda, Marcela; Ray, Nicholas; Barros, Nathan O.; Cavali, Jucilene; Costa, Carolina; Doria, Carolina R.; Fan, Joshua; et al. (Springer Nature, 2025)
Aquaculture in the Amazon holds the potential to meet increasing food demands while offering economic opportunities in a region facing deforestation and biodiversity loss. However, expanding aquaculture in this biodiverse region comes with complex environmental and social trade-offs. This Review explores how aquaculture can support sustainable development by minimizing its environmental impact, promoting equitable livelihoods and enhancing food security. It also highlights key challenges, such as greenhouse gas emissions and land-use changes, that need to be addressed for aquaculture to thrive sustainably in the Amazon.